RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Li, Chien-Feng; Chan, Ti-Chen; Wang, Cheng-I.; Fang, Fu-Min; Lin, Po-Chun; Yu, Shih-Chen; Huang, Hsuan-Ying (Angiogenesis (London), 2021)
Myxofibrosarcoma is genetically complex and lacks effective nonsurgical treatment strategies; thus, elucidation of novel molecular drivers is urgently needed. Reanalyzing public myxofibrosarcoma datasets, we identified mRNA upregulation and recurrent gain of RSF1 and characterized this chromatin remodeling gene. Myxofibrosarcoma cell lines were employed to elucidate the oncogenic mechanisms of RSF1 by genetic manipulation and two IL-1β-neutralizing antibodies (RD24, P2D7KK), highlighting the regulatory basis and targetability of downstream IL-1β-mediated angiogenesis. Tumor samples were assessed for RSF1, IL-1β, and microvascular density (MVD) by immunohistochemistry and for RSF1 gene status by FISH. In vivo, RSF1-silenced and P2D7KK-treated xenografts were analyzed for tumor-promoting effects and the IL-1β-linked therapeutic relevance of RSF1, respectively. In vitro, RSF1 overexpression promoted invasive and angiogenic phenotypes with a stronger proangiogenic effect. RT-PCR profiling identified IL1B as a top-ranking candidate upregulated by RSF1. RSF1 required hSNF2H and CEBP/β to cotransactivate the IL1B promoter, which increased the IL1B mRNA level, IL-1β secretion and angiogenic capacity. Angiogenesis induced by RSF1-upregulated IL-1β was counteracted by IL1B knockdown and both IL-1β-neutralizing antibodies. Clinically, RSF1 overexpression was highly associated with RSF1 amplification, IL-1β overexpression, increased MVD and higher grades (all P ≤ 0.01) and independently predicted shorter disease-specific survival ( P = 0.019, hazard ratio: 4.556). In vivo, both RSF1 knockdown and anti-IL-1β P2D7KK (200 μg twice weekly) enabled significant growth inhibition and devascularization in xenografts. In conclusion, RSF1 overexpression, partly attributable to RSF1 amplification, contributes a novel proangiogenic function by partnering with CEBP/β to cotransactivate IL1B , highlighting its prognostic, pathogenetic, and therapeutic relevance in myxofibrosarcomas.